Exploring community pharmacists' knowledge, perception and experiences towards branded and generic medicines in Kuwait: Highlighting the role of pharmacist - M. Al Hussaini; N. Alsaffar; A. Abdulraheem (Faculty of Pharmacy, Cairo University, 2018)
Background: Substituting brand drugs with generic drugs without affecting patients' health is considered a cost-effective measure to reduce health care expenditure. Objectives: The study was designed to explore the community pharmacists' knowledge, perception and experiences toward generic drug substitution and highlight the role of pharmacist in practicing substitution. Method: A descriptive cross sectional survey among community pharmacists was carried out in Kuwait. A validated questionnaires consisting of 3 sections with total of 22 questions were distributed to 180 pharmacists and collected after 3-5 days. Results: Less than half of respondents (46.1%) thought that generic drugs are equivalent to the original brands. 60% of pharmacists believed that OTC are as effective as brands while only 42% agreed that generic drugs can be as effective as brand for chronic diseases. Pharmacists agreed that brands have more strength variety (74%), better packaging (72%) and more expensive (66.2%) than generic. Most of the pharmacists agreed on stocking brand (88%) and generic (72%). Also 81% and 62% agreed that drug price and doctor's opinion could affect patients' choice, alternatively. 88% of pharmacists would recommend generic substitutes when brands are not available. Whereas 45% would try to persuade patients to shift to a brand when patient is unsatisfied with the generic. Pharmacists were more confident in recommending generic OTC drugs than the branded counterpart for chronic diseases (p = 0.001). Conclusion: A national brand substitution policy should be formulated and implemented to assist pharmacists in the proper substitution practice and to help minimize the healthcare costs.